The Contribution of Gender and Power to Perceptions of Physical Health, Mental Health, and Happiness: The National Social Life, Health, and Aging Project - Odlum, EdD, MPH, Michelle; Brewer, DrPH, MPH, Russell; Preston, PhD, MPH, Michael; Davis, PhD, RN, Nicole; Black, MA, MPH, Danielle (International Journal of Innovative Research in Medical Science, 2017)
Objective: Imbalances in societal power and associated gender norms can have adverse effects on health perceptions and resulting health behaviors. Aging further contributes to poor health outcomes and to barriers associated with the underutilization of diagnostic, treatment, and prevention services. Our analysis sought to use the Theory of Gender and Power (TGP) to identify social, economic, and societal factors that influence women’s perceptions of their physical health, mental health, and happiness to support the development and/or modification of health interventions for this population. Methods: The TGP guided the characterization of socio-economic and contextual factors that potentially contribute to perceptions of health and happiness. Using data from the National Social Life, Health and Aging Project Wave 2 female participants (N=1,839); items relevant to the TGP constructs of: 1) Gender-specific norms; 2) Power and authority; and 3) Cathexis were considered for inclusion. Linear regression analysis was conducted to identify the underlying factors that contribute to differences between the outcomes of interest. Results: Our analysis identified items that significantly characterized perceptions of health and happiness mainly centered on interpersonal relationships. Conclusions: Identified factors confirmed previous findings and provide insight into aging-related aspects among women 57-85.